Evaluation of the Effect of Anti-Corrosion Coatings on the Thermal Resistance of Ground Heat Exchangers for Shallow Geothermal Applications - Gianluca Cadelano; Alessandro Bortolin; Giovanni Ferrarini; Paolo Bison; Giorgia Dalla Santa; Eloisa Di Sipio; Adriana Bernardi; Antonio Galgaro (Energies, 2021)
The materials and the technology used to build the ground heat exchangers significantly affect the heat transfer performance of a geothermal system, in addition to the local geological and hydrogeological context. Among expense items such as the coupled heat pumps and the applied drilling technology, the heat exchangers play a key role in the shallow geothermal market. For this reason, they are usually made with plastic. Metal tubes are not widely used because of corrosion issues, which can compromise the reliability of the system over time. According to best practices, metal is an unfavorable choice if the pipes are not made of corrosion resistant alloys, such as stainless steel, but the overall performance is strongly related to the heat transfer efficiency. In this study, laser-flash technique is applied on carbon steel samples with anti-corrosion coatings and on corrosion resistant materials (stainless steel grades used for pipes), thus, allowing the comparison of their thermophysical properties. These properties are used to evaluate each solution in terms of thermal resistance. This study demonstrates that there are no particular corrosion resistant steel pipe configurations that are thermally favorable over others in a critical way.